Sharia-compliant financing as fiscal policy instrument: an Islamic economic approach to budget deficit management - Kartika Marella Vanni; Muchlis Yahya; Ali Murtadho; Fita Nurotul Faizah (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2025)
Budget deficits are a recurring fiscal challenge for many countries, including Indonesia, where reliance on conventional financing methods such as interest-based debt often imposes long-term economic burdens. This study explores the potential of Islamic financial instruments as an alternative solution to address budget deficits, emphasizing sustainability, fairness, and compliance with sharia principles. Using a qualitative approach through literature review and descriptive analysis, the research examines the implementation and effectiveness of instruments such as sukuk, crowdfunding, and securities crowdfunding based on sukuk. The findings reveal that these sharia-compliant tools not only provide viable financing options without the burden of interest but also foster public participation and uphold social justice principles. The study highlights the importance of strengthening regulatory frameworks and integrating Islamic financial systems into national fiscal policies to create a more inclusive, stable, and ethical financing ecosystem. The implications of this research underscore the potential of Islamic finance to contribute to sustainable economic development while adhering to ethical and religious values.